Regeneration of cofactor NAD(P)+ with NAD(P)H oxidase for the production of value-added chemicals - Zhou, Li-Jian; Long, Shuai-Xi; Huan, Tong; Wu, Yue; Zhang, Ye-Wang (Frontiers in Bioengineering and Biotechnology, 2025)
Nicotinamide adenine dinucleotide (phosphate) oxidases are the enzymes that catalyze the oxidation of NAD(P)H to produce NAD(P)+, which is the cofactor of many dehydrogenases. To reduce costs, cofactor regeneration of NAD(P)+ is essential for both enzymatic and whole-cell biotransformations. In the present review, the enzymatic or microbial production of rare sugars like L-tagatose, L-xylulose, L-gulose, and L-sorbose with cofactor regeneration was summarized. And the cofactor regeneration in some value-added chemicals, including acetoin, 1,3-dihydroacetone, vanillic acid, chlorolactone, acetophenone, and kinetic resolution of racemic phenylethanol by employing NADH/NADPH oxidase was also reviewed. The engineering of these enzymes by modifying the enzyme surface, reshaping the catalytic pocket, and mutating the substrate-binding domain of NADH oxidase to improve the catalytic performance for potential industrial applications was discussed in the future outlook.